Out of the core: the impact of focal ischemia in regions beyond the penumbra - Koukalova, Ludmila; Chmelova, Martina; Amlerova, Zuzana; Vargova, Lydia (Frontiers in Cellular Neuroscience, 2024)
The changes in the necrotic core and the penumbra following induction of focal ischemia have been the focus of attention for some time. However, evidence shows, that ischemic injury is not confined to the primarily affected structures and may influence the remote areas as well. Yet many studies fail to probe into the structures beyond the penumbra, and possibly do not even find any significant results due to their short-term design, as secondary damage occurs later. This slower reaction can be perceived as a therapeutic opportunity, in contrast to the ischemic core defined as irreversibly damaged tissue, where the window for salvation is comparatively short. The pathologies in remote structures occur relatively frequently and are clearly linked to the post-stroke neurological outcome. In order to develop efficient therapies, a deeper understanding of what exactly happens in the exofocal regions is necessary. The mechanisms of glia contribution to the ischemic damage in core/penumbra are relatively well described and include impaired ion homeostasis, excessive cell swelling, glutamate excitotoxic mechanism, release of pro-inflammatory cytokines and phagocytosis or damage propagation via astrocytic syncytia. However, little is known about glia involvement in postischemic processes in remote areas. In this literature review, we discuss the definitions of the terms "ischemic core", "penumbra" and "remote areas." Furthermore, we present evidence showing the array of structural and functional changes in the more remote regions from the primary site of focal ischemia, with a special focus on glia and the extracellular matrix. The collected information is compared with the processes commonly occurring in the ischemic core/penumbra. Moreover, the possible causes of this phenomenon and the approaches for investigation are described, and finally, we evaluate the efficacy of therapies, which have been studied for their anti-ischemic effect in remote areas in recent years.